Coverage Vol. 14 No. 2 - Journal, AUSTENIT (AUSTENIT, 2022)
Austenit is a peer-reviewed journal that is regularly published twice times (April and October) a year by Mechanical Engineering Department of Politeknik Negeri Sriwijaya and managed by an experienced editorial board coming from universities in Indonesia and overseas partners. This journal is a highly quality to bridge the results of applied and vocational research in the form of scientific works which have never been published in the other media. The works are in the field of mechanical engineering which includes product design and engineering, energy conversion, metallurgy engineering and sciences, construction, mechanical maintenance and repair, renewable energy and sustainability, and mechanization-control. There are eleven articles in this Vol.14 No.2 edition issue written by researchers practitioners from Indonesia. The Indonesian researchers from Politeknik Perkapalan Negeri Surabaya, Politeknik Negeri Indramayu, Politeknik Negeri Bandung, Politeknik Industri ATMI, Politeknik Astra, Institut Sepuluh Nopember Surabaya, Universitas Bangka Belitung, Universitas Sriwijaya, Universitas Tridinanti, Universitas TamanSiswa Palembang and Politeknik Negeri Sriwijaya. Each article has been selected by the editorial team and passed the single-blind review stage by qualified reviewers in the field. Warm Regards, Chief Editor AUSTENIT (eISSN:2622-7649)